1985
DOI: 10.1007/bf00905724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a primary prevention program for children of divorce

Abstract: The effectiveness of a primary prevention program for children of divorce is evaluated. Subjects included 82 mother-child pairs. Mothers had been separated for 33 months or less and did not have prior histories of using mental health services. Subjects were assigned to one of four conditions: (a) the Children's Support Group alone (CSG), (b) the CSG and the Single Parents' Support Group (SPSG), (c) the SPSG alone, or (d) a no-treatment control group. Data collected before, after, and 5 months following interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
5

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 18 publications
3
69
1
5
Order By: Relevance
“…Both programs provide support to children and teach anger control, relaxation, and communication skills and are supported by quasiexperimental and experimental research studies. In a quasi-experimental study, the CSG program of the Divorce Adjustment Project (DAP) (Stolberg, Cullen, & Garrison, 1982) has been shown to improve the self-esteem and social skills of 7-to 13-year-old children (Stolberg & Garrison, 1985). An experimental study of third-through fifth-grade children who participated in CSG indicated that they experienced reductions in internalizing and externalizing behavior problems (Stolberg & Mahler, 1994).…”
Section: The State Of the Art In Evaluationmentioning
confidence: 98%
“…Both programs provide support to children and teach anger control, relaxation, and communication skills and are supported by quasiexperimental and experimental research studies. In a quasi-experimental study, the CSG program of the Divorce Adjustment Project (DAP) (Stolberg, Cullen, & Garrison, 1982) has been shown to improve the self-esteem and social skills of 7-to 13-year-old children (Stolberg & Garrison, 1985). An experimental study of third-through fifth-grade children who participated in CSG indicated that they experienced reductions in internalizing and externalizing behavior problems (Stolberg & Mahler, 1994).…”
Section: The State Of the Art In Evaluationmentioning
confidence: 98%
“…Stolberg et al (Stolberg, Cullen, & Garrison, 1982;Stolberg & Garrison, 1985) developed a 12-week school-based intervention, the Children's Support Group, within the larger Divorce Adjustment Project for 8-13 year old children and their mothers. Subjects were assigned to one of four conditions: child intervention only, parent intervention only, combined parent and child intervention, and no treatment control.…”
mentioning
confidence: 98%
“…L'identification et l'expression des sentiments, la gestion de la colère, l'affirmation de soi, l'acquisition d'habiletés de résolution de problèmes et la mutualisation au sein d'un groupe de soutien comptent donc parmi les objectifs d'intervention les plus fréquents (Drapeau et a/., 1993a(Drapeau et a/., , 1993bMireault et a/., 1991 ;Pedro-Caroll et Cowen, 1987 ;Stolberg et Garrisson, 1985). Les problèmes sociaux évoqués dans la présentation des programmes concernent les troubles de comportement, les retards scolaires et les déficits dans le développement psychosocial.…”
Section: Objectifs Thèmes Et Méthodesunclassified
“…Dans le CSG, les parents n'assistent pas aux groupes d'enfants mais les mères -non les pères -sont conviées à un groupe parallèle. Stolberg et Garrisson (1985) ont constaté que les enfants dont les mères ne participaient pas au groupe d'adultes réalisaient des gains significativement plus élevés sur le sentiment de compé-tence et sur les habiletés d'adaptation sociale. De même, les mères dont les enfants ne participaient pas au CSG présentaient des gains d'ajustement significativement plus élevés.…”
Section: Participation Des Parentsunclassified